EFL Teacher Intervention in Mediating Students’ Interaction in Web-Based Collaborative Writing Environment Using Google Docs - Titin Purwaningtyas; Joko Nurkamto; Diah Kristina (VELES Voices of English Language Education Society, 2023)
The level of teacher’s assistance in web-based collaborative writing activities affected students’ collaboration and non-collaboration. Therefore, the teacher’s role in enhancing students’ active learning was inseparable. This study focused on the EFL teacher moves in facilitating groups’ work of writing using web-based tool, Google Docs to support online learning. Conducting collaborative work in writing technology was valuable for promoting students’ participation and collaboration. The participant in this qualitative research case study was an EFL teacher at an Indonesian vocational high school. The data was based on a semi-structured interview and document analysis of students’ worksheet and teacher-students’ written conversation in Google Docs. The findings showed that web-based medium facilitated the teacher assisted the students’ engagement through organisational, socio-cognitive, and socio-affective in collaborative writing environment. Significantly, the teacher favorably convenience to deliver electronic feedback and monitoring students’ progress quickly. Unfortunately, students’ issues (e.g. less collaboration, cheated on the internet), and technical issues (e.g. unstable internet connection, low devices’ specification) were commonly problems encountered by the teacher.  Google Docs as a web-based medium was valuable to help the teacher in creating groups’ work in teaching online writing. This research implies that the teacher might be more concerned on selecting appropriate types of intervention and utilize suitable media to support teaching’s styles by enriching technology skills’ training. In addition, students could enjoyed and acquired benefits from having the teacher's help to be more collaboratively work in constructing text with their teammates.